LEADERSHIP STYLE, COMPENSATION, TRAINING, AND MOTIVATION ON EMPLOYEE PERFORMANCE OF PT. HASAN PRATAMA KARTASURA - Wahyudianto, Anang; Sudarwati, Sudarwati; TS, Kartika Hendra (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to determine and explain the effect of Leadership Style, Compensation, Training, and Motivation on Employee Performance of PT. Hasan Pratama Kartasura. The population of this study was 65 employees of PT. Hasan Pratama Kartasura with saturated samples. Data collection using a questionnaire. Data analysis techniques using the Multiple Linear Analysis method. The results of the study showed that Leadership Style, Compensation, Training, and Motivation on Employee Performance of PT. Hasan Pratama Kartasura has a positive and significant influence by contributing to Performance by 82.3% while the remaining 17.7% is explained by other variables not proposed in this study. Suggestions from this study, employees of PT. Hasan Pratama Kartasura can improve training and motivation in the leadership style applied in the company in order to get compensation that is in accordance with performance.Keywords: Performance, Leadership Style, Compensation, Training, Motivation, Employees